Roles : "I am as intently observed as the people photograph" - Pelser, Monique Myren (Rhodes University, Faculty of Humanities, Department of Fine Art, 2007)
With this dissertation I propose an investigation of how the photographic portrait attempts to construct and confirm identity through the representation of types. Drawing from theoretical texts by Roland Barthes and Robert Sobieszek and engaging with my own process of self-portraiture, as a means of troubling the usual power relations involved between the photographer and the sitter, I will demonstrate the dialectical nature of these roles involved in photographic portraiture. Looking at Pieter Hugo's portraits of judges in Botswana permits me to deal with issues of masquerade and how fashions and uniforms mask an individual allowing him/her to perform roles and stereotypes in society. Referring to another set of Hugo's images from his ongoing series Looking Aside, I will explore the paradoxical nature of the portrait through the dialectic of the 'self 'and 'other' subject and object split through an exploration of notions of skin and prosthetic skin and the relationship to the liminal space 'opened' between subject and object, or viewer and image.
Keywords: Hugo, Pieter; Portrait photography; Self-portraits; Photography, Artistic -- Philosophy